On the systematic of the water mite Piona laminata (Thor, 1901) (Acari, Hydrachnidia, Pionidae) - Tuzovskij, Petr V. (Zootaxa, 2019)
The first description of larva and deutonymph, and redescription of male and female of the water mite Piona laminata (Thor, 1901) (Acari, Hydrachnidia, Pionidae) are given.